Phytoplankton size-distribution and community structure in relation to mucilage occurrence in the northern Adriatic Sea - Totti, C.; Cangini, M.; Ferrari, C.; Kraus, R.; Pompei, M.; Pugnetti, A.; Romagnoli, T.; Vanucci, S.; Socal, G. (Science of the Total Environment, 2005)
The spatial and temporal variations of pico-, nano- and microphytoplankton abundance and composition were investigated over a 37 month period, focusing on the ecological role of different size classes of phytoplankton, and on the changes of the community structure that might occur during periods when large mucilage macroaggregates appear. Samples were collected monthly from June 1999 to July 2002 at 11 stations, along three transects covering the northern Adriatic basin. Highest abundances were observed in late-winter/spring for microphytoplankton (mainly diatoms), in spring-summer for nanophytoplankton, and in summer for picophytoplankton. The autotrophic component was more abundant in the summers of 2000 and 2002 (when large mucilage aggregates occurred) than in the summers of 1999 and 2001 (when a massive phenomenon was not observed). This increase was statistically significant for pico-, nano- and, among microphytoplankton, only for dinoflagellates. Blooms of picophytoplankton were often observed at the bottom layer during mucilage summers. The microphytoplankton community during mucilage phenomena was characterized by a species composition (Chaetoceros spp., Cerataulina pelagica, Pseudo-nitzschia delicatissima, P pseudodelicatissima, Cylindrotheca closterium, Dactyliosolen fragilissimus) comparable to that observed in summers without extensive mucilage occurrence. However, some species appeared with significantly higher densities in the summers of 2000 and 2002: Ceratium furca, C closterium, Oxytoxum spp., Hemiaulus hauckii and Gonyaulax fragilis. Microscopic observation of aggregates revealed that the microphytoplankton species composition inside the aggregates was comparable to that observed in the water column, with an enrichment of opportunistic species such as C closterium and P. delicatissima. The presence of mucilage aggregates affects the phytoplankton populations in the water column, even when aggregates are at early stages. It seems that there is a mutual relationship between phytoplankton and aggregates, i.e., several diatom and dinoflagellate species may contribute to the aggregate formation and enlargement, but mucilage aggregates themselves may also affect the phytoplankton populations, allowing the development of a rich diatom community and in general enhancing nanophytoplankton growth. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: abundance; Coastal waters; dynamics; ecology; Ecosystems; microphytoplankton; mucilage aggregates; nanophytoplankton; nanoplankton; northern adriatic sea; Nutrients; picophytoplankton; picoplankton; release; variability

Populations of exopolysaccharide-producing cyanobacteria and diatoms in the mucilaginous benthic aggregates of the Tyrrhenian Sea (Tuscan Archipelago) - De Philippis, R.; Faraloni, C.; Sili, C.; Vincenzini, M. (Science of the Total Environment, 2005)
The microalgal community of benthic mucilages sampled in various sites of the Tuscan Archipelago during the period May 1999-July 2002, was always dominated by diatoms. Synedra, Licmophora and Navicula were the most frequently found genera, their presence having been observed within all the period under study; other ten genera of diatoms were found in the benthic mucilages, but their presence was dependent on the month and the year of observation. As concerns the cyanobacterial community, the filamentous genera Leptolyngbya, Lynghya and Rivularia were the most frequently found, independently on the period and the year of samplings, while other genera, namely Oscillatoria, Symploca, Aphanocapsa and Gloeocapsa, were less frequently observed. During the period under study, the highest number of different genera of diatoms and cyanobacteria in the mucilaginous aggregates was observed during summer periods, particularly in June and July. The microscopic observation of the samples demonstrated that only diatoms belonging to the genera Navicula, Amphora, Cylindrotheca and Pseudo-nitzschia possessed outermost polysaccharidic investments, the cells of the other genera being devoid of sheaths or capsules. On the other side, all the observed cyanobacteria, with the exception of Oscillatoria strains, were characterized by the presence of outermost polysaccharidic investments, most frequently in the form of sheaths. However, when the microalgal and cyanobacterial isolates were cultured under laboratory conditions, the release of polysaccharidic material into the culture medium was observed only in a few cases and always in very small amounts.The observations done on the natural samples and the results obtained with the cultures of the microalgae and cyanobacteria isolated from the benthic aggregates suggest that only diatoms have given some contribution to the formation of the polysaccharidic material constituting the matrix of the mucilages, whereas the role of cyanobacteria in the benthic aggregates seems to be related to their capability to create biofilms on solid surfaces, constituting the first step in the colonization of the benthic surfaces by the microbial community. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: batch cultures; benthic aggregates; benthic mucilages; communities; cyanobacteria; diatoms; exopolymer particles tep; exopolysaccharides; Marine; origin; phytoplankton; polysaccharides; release; sedimentation; tyrrhenian sea